TRYING TO DETERMINE THE DEVELOPMENT TRENDS OF THE RUSSIAN ECONOMY - A. A. Frenkel; Ya. V. Sergienko; N. N. Volkova; O. N. Matveeva (Финансы: теория и практика, 2017)
The paper deals with the development of integral indices to assess the overall state of the economy. A method of calculating three indices is described: leading, synchronous and lagging with the focus on the leading index that detects turning points in the dynamics of the economy. All the three indices are calculated for the Russian economy as of 1999-2015; the forecast for April 2016 was made with the prediction error of 2.3%. The analysis of the results leads to the conclusion that the value of the lead lag has decreased compared with the previous periods and this is an evidence of the increased rate of changes in the industrial production dynamics. Moreover, the difference between the lead (4 months) and lag (6 months) of the leading and lagging indices, respectively, relative to the rate of change in the industrial production reflects the specifics of the structure of the Russian economy which is dominated by the export-oriented raw materials sector. In the calculation of an aggregate index, the problem of comparing partial indices having different economic meaning and measurement units is solved by significant adjustment of each index.